Soil Erosion on Abandoned Land in Andalusia: A Comparison of Interrill- and Rill Erosion Rates. (14th November 2012) - Wirtz, S.; Iserloh, T.; Rock, G.; Hansen, R.; Marzen, M.; Seeger, M.; Betz, S.; Remke, A.; Wengel, R.; Butzen, V.; Ries, J. B.
Abstract : The present paper is based on several field investigations (monitoring soil and rill erosion by aerial photography, rainfall simulations with portable rainfall simulators, and manmade rill flooding) in southern Spain. Experiments lead now to a closer understanding of the dynamics and power of different soil erosion processes in a gully catchment area. The test site Freila (Andalusia, Spain) covers an area of 10.01 ha with a rill density of 169 m ha −1, corresponding to a total rill length of 1694 m. Assuming an average rill width of 0.15 m, the total rill surface can be calculated at 250 m 2 (0.025 ha). Given that, the surface covered by rills makes up only 0.25% of the total test site. Since the rill network drains 1.98 ha, 20% of the total runoff comes from rills. The rills' sediment erosion was measured and the total soil loss was then calculated for detachment rates between 1685 g m −2 and 3018 g m −2 . The interrill areas (99.75% of the test site) show values between 29 and 143 g m −2 . This suggests an important role of rill erosion concerning runoff and soil detachment.